Detection of elements in slimming tea product by using laser induced breakdown spectroscopy - Safie, Saleha (2014)
Laser induced breakdown spectroscopy (LIBS) has been applied to determine the element content in slimming tea product. A Q-switched Nd:YAG laser operating at 1064 nm and generating 93.7 mJ per pulses was employed to excite the pellet sample and the fluorescence emission was analyzed via spectrum analyzer. The induced spectral lines were compared with National Institute of Standards and Technology (NIST) database to identify the element. A commercial slimming tea was used as sample to be investigated whereas the natural tea leaves were used as control. The LIBS results showed that both slimming tea and natural tea leaves contain several elements including iron (Fe), sodium (Na), chromium (Cr), cobalt (Co), calcium (Ca), manganese (Mn), magnesium (Mg), silicon (Si), sulfur (S), titanium (Ti), nickel (Ni) and cesium (Cs). However, higher intensity of elements was found in slimming tea spectrum compared to natural tea leaves. The plasma temperatures calculated using Boltzmann plot were found to be 13588.95 K and 12319.50 K for slimming tea and tea leaves samples respectively whereas the electron density for slimming tea and tea leaves samples were 7.46 × 1016 cm-3 and 15.91 × 1016 cm-3, respectively. The plasma produced by this LIBS system was found to be in local thermodynamic equilibrium (LTE) condition after evaluating these plasma parameters. Quantitative analysis performed by using inductively coupled plasma mass spectroscopy (ICPMS) proved that the concentration of the elements is higher in slimming tea than in natural tea leaves.